Menggoyang Ruang Isolasi dalam Dunia Pendidikan: Berteologi di Tengah Masyarakat Plural - Romelus Blegur; Grace Enting Alfrianne Illu (Didache: Journal of Christian Education, 2023)
Restricting the space for the freedom of other religions to become an issue that continues to surface until now, and this has damaged the fact of plurality. Coexistence among religious adherents is a serious problem characterized by fanatical attitudes that isolate religious adherents for theological reasons. This then led to religious warnings that propagated in various sectors of human life including education. To overcome this problem, the purpose of this research is to provide space for theology to exist through the role of Christian education to shake up the space of isolation which continues to narrow relations between religious adherents. The method used in this research is content analysis concerning texts related to research topics in the form of journal articles, books, and online media which are selected according to research interests. The result of this study is that the role of education is needed as a vehicle for educating the intelligence of religious adherents in realizing theology both explicitly and implicitly in a pluralistic society. Through educated people, the isolation space can be shaken, and theology can exist creatively and proportionately in caring for the diversity of religious life.